Adaptive sliding mode control design for the attitude of the quadrotor unmanned aerial vehicle (UAV) - Eltayeb, Ahmed; Mohd Fua’ad, Rahmat; Mohd Ariffanan, Mohd Basri; Mansour, Mohammed A. M. (IOP Publishing, 2020)
In this article, the adaptive sliding mode controller (ASMC) is developed for the quadrotor attitude subsystem. The proposed ASMC controller aims to reduce/decrease the unwanted chattering phenomena associated with the conventional sliding mode controller, and meanwhile achieving a robust trajectory tracking for the attitude. The stability of the proposed (ASMC) controller has been verified based on Lyapunov stability theorem. The quadrotor UAV model and the performance of the proposed controller have been simulated and tested by simulation using MATLAB/SIMULINK environment. The simulation result is proof that the chattering has been reduced significantly.